Association of pneumococcal conjugate vaccination with rates of ventilation tube insertion in Denmark: population-based register study. Issue 6 (5th June 2015) - Groth, Christina; Thomsen, Reimar W; Ovesen, Therese
Abstract : Objective: To examine if the introduction of pneumococcal conjugate vaccine (PCV) in Denmark was associated with a decrease in the rate of ventilation tube (VT) insertions performed by office-based practising ear, nose and throat (ENT) specialists. Design: Population-based register study based on prospectively collected data. Setting: Central Denmark Region. Data on VT insertions performed by any office-based practising ENT specialist in the region were collected from the National Health Service Registry. Participants: All children below the age of 2 years with a first-time VT insertion from 2001 through 2011. Main outcome measures: Age-stratified and gender-stratified standardised incidence rates of first-time VT insertion, and incidence rate ratio for PCV period 2008–2011 compared with pre-PCV period 2001–2007. Results: The annual incidence rate of first-time VT insertion in small children increased steadily from 64/1000 person-years in 2001 to 100/1000 person-years in 2011. The incidence rate ratio was 1.27 (95% CI 1.24 to 1.30) in the PCV period compared with the pre-PCV period. Conclusions: The introduction of PCV into the Danish childhood immunisation programme in 2007 was not associated with a subsequent decrease in the rate of VT insertions among children below the age of 2 years. Instead, the rate continued to rise, as before the introduction of PCV. Trial registration number: Danish Data Protection Agency: 2007-58-0010.